Transitioning to Unfractionated Heparin in Treatment of Non-ST-Segment Elevation Myocardial Infarction Patients on Direct Oral Anti-Xa Inhibitors: Management of NSTEMI patients in DOAC - Mohamed Tashani; Raice A. Stevens; Bruno de Souza Goncalves; Hari Vishal Lakhani; Sharon E jones; Laura Given; Rebecca Sicking; Thomas Dougherty; Ellen Thompson; Komal Sodhi; Rameez T Sayyed; Mehiar El-Hamdani; et al. (Cellular and Molecular Biology, 2023)
The heparin anti-Xa assay is affected by the use of direct oral anticoagulants (DOACs) and is utilized in the management of intravenous unfractionated heparin. Patients with non-ST-segment myocardial infarction (NSTEMI) receive intravenous unfractionated heparin with prior administration of DOACs poses challenges given these laboratory abnormalities. On this background, we evaluate if an elevated heparin anti-Xa assay may lead to the decision to delay heparin in the management of NSTEMI patients and the outcome of in-hospital mortality. This is a single-center chart review study with patients admitted between January 2019 and December 2020. Patients with a documented DOAC home medication and a diagnosis of NSTEMI were included. Data was collected for heparin anti-Xa levels at baseline, after 6 and 12 hours of hospitalization, in addition to the reason for the delay in the administration of heparin. Statistical analysis included the determination of r-squared correlation and one-way ANOVA using GraphPad Prism 8.0. A total of 44 patients were divided into three groups based on baseline Xa levels of patients. Elevated Xa level was noted more in patients who were taking apixaban. Heparin infusion was delayed among this sub-group of patients. Elevated baseline heparin anti-Xa levels were significantly improved after 12 hours. There was no correlation between elevated anti-Xa levels and activated partial thromboplastin time. No in-hospital mortality was observed among any of the subgroups. Collectively, this study demonstrates that the high sensitivity of heparin anti-Xa assay to DOACs affect assay accuracy and result in elevated heparin anti-Xa level with the use of DOACs resulting in delayed start of heparin therapy in treating NSTEMI patients.